#### Answer

$f'(x) = -3x^{0.5}+6x^{-0.5}$

#### Work Step by Step

In order to derivate this function you have to apply the power rule:
$\dfrac{d}{dx}(x^n)=nx^{n-1}$
$f'(x) = -2(1.5)x^{0.5}+12(0.5)x^{-0.5}$
$f'(x) = -3x^{0.5}+6x^{-0.5}$

Published by
Pearson

ISBN 10:
0321749006

ISBN 13:
978-0-32174-900-0

$f'(x) = -3x^{0.5}+6x^{-0.5}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.